Neuropathic pain in patients with haemophilia, that is the question - Krüger, S.; Hilberg, T. (Hämostaseologie, 2015)
Chronic pain caused by recurrent joint bleedings affects a large number of patients with haemophilia (PwH). The basis of this pain, nociceptive or neuropathic, has not been investigated so far. In other pain-related chronic disorders such as osteoarthritis or rheumatoid arthritis, initial studies showed nociceptive but also neuropathic pain features. 137 PwH and 33 controls (C) completed the painDETECT-questionnaire (pDq), which identifies neuropathic components in a person´s pain profile. Based on the pDq results, a neuropathic pain component is classified as positive, negative or unclear. A positive neuropathic pain component was found in nine PwH, but not in C. In 20 PwH an unclear pDq result was observed. In comparison to C the allocation of pDq results is statistically significant (p≤0.001). Despite various pDq results in PwH and C a similar appraisal pain quality, but on a different level, was determined. Summarising the results, there is a potential risk to misunderstand underlying pain mechanisms in PwH. In chronic pain conditions based on haemophilic arthopathy, a differential diagnosis seems to be unalterable for comprehensive and individualised pain management in PwH.
Keywords: Haemophilia; neuropathic; nociceptive; pain